Enhancing herbaceous perennial stock production through the application of plant growth regulators for Heuchera sanguinea 'Snow Angel' and Zauschneria garrettii ‘PWWGO1S' Orange Carpet® - Markovic, Sean, author; Klett, Jim, advisor; Newman, Steven, committee member; Pilon-Smits, Elizabeth, committee member (Colorado State University. Libraries, 2018)
Commercial growers throughout the Rocky Mountain Region have an increased commercial demand for sustainable herbaceous perennial plants. Greenhouse production for these adaptable perennials has resulted in problems with stock plant management and propagation. The objective of this study was to determine the efficacy for increased vegetative growth of three dissimilar plant growth regulators applied as foliar sprays on the vegetative growth of Heuchera sanguinea 'Snow Angel' and Zauschneria garrettii 'PWWGO1S' ORANGE CARPET® propagation stock plants in number one (2.84L) containers. Three chemical plant growth regulators were applied at two different rates: 1) Ethephon (2-chloroethyl Phosphonic Acid) (200 and 400 mg·L–1 (ppm)) (Verve, Nufarm Americas, Inc., Alsip, IL), 2) 6-benzylaminopurine (250 and 500 mg·L –1) (Configure; Fine Agrochemicals Limited, Worcester, U.K.), and 3) Gibberellins A4A7 (GA) & N-(phenylmethyl)-1H-purine 6-amine (50 and 100 mg·L–1) (Fascination; Valent USA Corp., Fresno, CS). Twelve replications of the two taxa were evaluated every month for a period of four months for plant height, width, number of cuttings, and fresh & dry weight of the cuttings. This study was replicated twice, the first experiment was performed from November 2016 to March 2017, and the second experiment was performed from August 2017 to December 2017. The two experiments conducted at different times of the year gave an indication of a better time of year for stock production of these two herbaceous perennials. Heuchera performed better in the first experiment from November to March. The Zauschneria plants performed better during the second experiment from August to December. Heuchera plants that received Fascination (A4A7 (GA) & N-(phenylmethyl)-1H-purine 6-amine) treatments at 50 and 100 mg·L–1 and Configure (6-benzylaminopurine) at 400 mg·L–1 concentrations resulted in 17%, 22%, and 20% more cuttings taken than control plants. Both concentrations of Ethephon treated Heuchera plants were statistically similar to control plants. Zauschneria plants that received Fascination (A4A7 (GA) & N-(phenylmethyl)-1H-purine 6-amine) treatments at 50 and 100 mg·L–1and Configure (6-benzylaminopurine) at 200 mg·L–1 concentrations resulted in 14%, 16%, and 10% more cuttings, respectively. However, Zauschneria plants that received Fascination (A4A7 (GA) & N-(phenylmethyl)-1H-purine 6-amine) treatments at 50 and 100 mg·L–1 had a decrease of 13% and 14% for the fresh weight of cuttings taken when compared to the control. Configure (6-benzylaminopurine) treatments also resulted in a visual decrease in reproductive growth. The different applications of the plant growth regulators resulted in a wide variety of cutting sizes and water content; this is based on the differences seen per treatment in the fresh and dry weights collected. A secondary rooting study was conducted after each stock plant experiment. Cuttings were harvested from each treatment combination after four weeks; May 16, June 13, and July 11, 2017 for the first experiment and January 11, February 8, and March 1, 2018 for the second experiment. Cuttings were taken at the same time of day, in the morning, and stuck in trays of 98 or 72 cells filled with Jiffy® Preforma media and placed under mist with bottom heat at a temperature of 18.3 or 23.9 degrees Celsius for Heuchera and Zauschneria respectively. Rooting percentages and number of visible roots were then collected every week for four weeks. Rooting of the two taxa resulted in no statistical differences observed between the treatments and the control. This gave the indication that the use of plant growth regulators during stock plant production would not result in decrease rooting of the harvested cuttings. In conclusion, the use of plant growth regulators resulted in increases in propagation material produced by stock plants of both taxa. A Fascination (A4A7 (GA) & N-(phenylmethyl)-1H-purine 6-amine) treatment between 50 and 100 mg·L–1 is recommended in Heuchera sanguinea stock plant production for its increase in cuttings available at each harvest event. A Configure (6-benzylaminopurine) at 200 mg·L–1treatment is recommended for Zauschneria garrettii stock plant production due to the increase in quality vegetative propagation material.